Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Heat Transfer, Volume 7 2002
DOI: 10.1115/imece2002-33733
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Foam Thermosyphon Evaporator Performance: Parametric Investigation of the Effects of Working Fluid, Liquid Level, and Chamber Pressure

Abstract: Graphite foams have recently been developed at ORNL and are beginning to be applied to thermal management of electronics. These foams consist of a network of interconnected graphite ligaments whose thermal conductivities are up to five times higher than copper. The thermal conductivity of the bulk graphite foam is similar to aluminum, but graphite foam has one-fifth the density of aluminum. This combination of high thermal conductivity and low density results in a thermal diffusivity about four times higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Coursey et al [10] studied the effects of working fluid, liquid level and chamber pressure on a graphite foam thermosyphon with PF-5060 and PF-5050 as the working fluids. They determined that lower operating pressures resulted in higher heat fluxes (10-70 W/ m 2 K) and different working fluids and fill ratios did not affect thermosyphon performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coursey et al [10] studied the effects of working fluid, liquid level and chamber pressure on a graphite foam thermosyphon with PF-5060 and PF-5050 as the working fluids. They determined that lower operating pressures resulted in higher heat fluxes (10-70 W/ m 2 K) and different working fluids and fill ratios did not affect thermosyphon performance.…”
Section: Introductionmentioning
confidence: 99%
“…Marinite insulation saturation saturation temperature of fluid Teflon measured at Teflon lip up power moving towards test section dielectrics [8][9][10][11]. The effects of flux levels, fill ratio and condenser operating temperature on the overall thermal performance, including thermal resistance and heat transfer coefficient are examined.…”
Section: Introductionmentioning
confidence: 99%
“…Mudawar and Anderson [4] performed saturated as well as subcooled pool-boiling experiments using multilevels of low profile surfaces (microfins, microgrooves, and microstuds) and reported that the critical heat flux ("CHF") of 159.3 W/cm could be achieved at wall super heat of 65 C and liquid subcooling of 35 C using FC-72 as a working fluid. Coursey et al [5] explored the applicability of graphite foams to thermal management of electronic devices. The foams are composed of graphite ligaments which are reported to have thermal conductivity values (up to five times higher than for copper).…”
mentioning
confidence: 99%
“…The working fluid used in this experiment was PF-5060 (Manufacturer: 3M Co.). PF-5060 (which is 95% pure FC-72 [5]) was chosen as the working liquid as a cheaper substitute for FC-72. Both liquids have nearly identical boiling characteristics (e.g., latent heat of vaporization, saturation temperature, liquid and vapor densities as well as specific heats, etc.).…”
mentioning
confidence: 99%
“…They reported heat transfer rates up to 100 W/cm 2 g . The use of graphite foam as the evaporator in a thermosyphon was investigated by Coursey et al [33]. These foams consist of a network of interconnected graphite ligaments whose thermal conductivities are up to five times higher than copper.…”
Section: Immersion Coolingmentioning
confidence: 99%